SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING PADA BENGKEL SEROJA MOTOR - Widia Nisnaini; Lalu Puji Indra Kharisma; Muhammad Azmi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
Bengkel Seroja Motor is a workshop as well as a shop located in Kotaraja Village, Sikur District, East Lombok Regency. Currently, the increasing number of employees who come from different educational backgrounds makes the diversity of employees also increasingly complex, making it difficult to choose the best employees. Therefore, it is necessary to develop a Decision Support System as an alternative solution, so as to increase efficiency and ef- fectiveness in the selection and improve quality in determining the best employees. The decision support system for determining the best employees uses the SAW (simple additive weighting) method based on predetermined criteria and weights. The criteria used as indicators are absenteeism, discipline, work attitude, responsibility, and per- formance. The SAW (simple additive weighting) method was chosen because it is able to select the best alternative from a number of alternatives. This research was conducted by looking for the weights on each attribute, then ranking to determine the best employees. In this study using the Waterfall methodology, which is a software development method that begins with ana- lyzing company needs, designing, building applications, to conducting trials. The results of this study are in the form of a decision support application, which can recommend the best employees at the Seroja Motor Workshop.